VD_FINDINFO ML / 2021 / 214 vom 28. Oktober 2021 - VD Tribunal cantonal (2021)
NOTIFICATION IRRÉGULIÈRE, DROIT D'ÊTRE ENTENDU, FÉRIES DE POURSUITE | 29 al. 2 Cst., 56 ch. 2 LP, 56 LP, 63 LP, 136 CPC (CH), 138 al. 1 CPC (CH), 138 al. 3 let. a CPC (CH)